Tὸ "Βιβλίο τοῦ Ἡρακλείδη" καὶ ἡ καταδίκη τοῦ Νεστορίου. Ἱστορικοκανονικὴ θεώρηση (Γρηγόρης, 2009)
The Book (or Treatise) of Heracleidis is known as the Apology of Nestorius. The comparative examination of its text with the Minutes of the Third Ecumenical Synod, throws new light on Nestorius´ trial and conviction, and brings to light new research elements, regarding the juridical procedures of the era. Last but not least, the survey reveals who is hiding under the pseudonym ῾Heracleidis῾. In contrast to what was beleived until today, the writer of the Treatise is not Nestorius, or a student of him, but, Hereneus of Tyros, his loyal friend and defense counsel before the Emperor, at Nestorius' trial.